2015
DOI: 10.3329/bjdre.v5i2.24716
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of cephradine in dental procedures: A observational study in Bangladesh

Abstract: Bacteremia is common with manipulation of the teeth and periodontal tissues during dental procedures. Majority of dental office visits result in some degree of bacteremia that warrants antibiotic prophylaxis before a dental procedure to reduce the frequency, nature or duration of bacteremia. This study aimed to collect data on prophylactic use of cephradine which is most preferred in dental procedures in Bangladesh.  A total 2219 of patients both adult and children above 5 years were enrolled to assess use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[19,20] Gingivitis was found in 33 (44%) cases in group A and 35 (46.7%) in group B while frequency of periodontitis was 37 (56%) in group A and 40 (53.2%) in group B. [21] Smoking was the most common cause of infection found in 38 (50.7%) in group A and 41 (54.7%) in group B followed by compromised oral hygiene 22 (29.3%) in group A and 18 (24%) in group B and diabetes among both groups were 15 (20%) and 16 (21.3%).Previous research presented the same findings in which infection may cause because of smoking and poor brushing. [22] We found that effectiveness in group B (Amoxicillin) was higher among 63 (84%) cases as compared to group A (Cephedrin).…”
Section: Therementioning
confidence: 99%
“…[19,20] Gingivitis was found in 33 (44%) cases in group A and 35 (46.7%) in group B while frequency of periodontitis was 37 (56%) in group A and 40 (53.2%) in group B. [21] Smoking was the most common cause of infection found in 38 (50.7%) in group A and 41 (54.7%) in group B followed by compromised oral hygiene 22 (29.3%) in group A and 18 (24%) in group B and diabetes among both groups were 15 (20%) and 16 (21.3%).Previous research presented the same findings in which infection may cause because of smoking and poor brushing. [22] We found that effectiveness in group B (Amoxicillin) was higher among 63 (84%) cases as compared to group A (Cephedrin).…”
Section: Therementioning
confidence: 99%